Enhancing antioxidant delivery through 3D printing: a pathway to advanced therapeutic strategies - Alogla, Ageel (Frontiers in Bioengineering and Biotechnology, 2023)
The rapid advancement of 3D printing has transformed industries, including medicine and pharmaceuticals. Integrating antioxidants into 3D-printed structures offers promising therapeutic strategies for enhanced antioxidant delivery. This review explores the synergistic relationship between 3D printing and antioxidants, focusing on the design and fabrication of antioxidantloaded constructs. Incorporating antioxidants into 3D-printed matrices enables controlled release and localized delivery, improving efficacy while minimizing side effects. Customization of physical and chemical properties allows tailoring of antioxidant release kinetics, distribution, and degradation profiles. Encapsulation techniques such as direct mixing, coating, and encapsulation are discussed. Material selection, printing parameters, and post-processing methods significantly influence antioxidant release kinetics and stability. Applications include wound healing, tissue regeneration, drug delivery, and personalized medicine. This comprehensive review aims to provide insights into 3D printing-assisted antioxidant delivery systems, facilitating advancements in medicine and improved patient outcomes for oxidative stress-related disorders.